Using curriculum differentiation to respond to students’ diversity - Sičiūnienė, Viktorija (Lietuvos matematikos rinkinys, 2021)
The article observes the results of the questionnaire of 1923 tenth-formers and their mathematics teachers. Statistical analysis of these results has been done using SPSS 13.0.The practice of curriculum differentiation in Lithuania is the subject of the observation.The research has shown that about 70 per cent of teachers more or less base their syllabus on the content of the textbook. The students’ achievements are dependent both on the teacher‘s understanding that syllabus has to be adapted to the students and ability to do that effectively. The following conclusion could be done: about 60 per cent of mathematics teachers should improve their competence in planning and developing syllabus.Organizing learning process about 80 per cent of teachers basically use reproductive teaching-learning method which requires little independent students’ activity. The institutions that prepare teachers and care about their competence should pay more attention to teachers’ qualification to apply teaching and learning methods in practice.The article has also observed the students and teachers’ understanding of principles and criteria and assessment used in schools and the quality of students’ feet-back.More attention should be paid to teachers’ competence providing faster and more efficient feet-back to students and help they need.
Keywords: mathematics; differentiation; syllabus planning; management of teaching-learning process; assessment for learning